The Influence of Influencers, Live Streaming, EWOM, and Flash Sales on Purchasing Decisions through Jiera Consumer Satisfaction in TikTok Shop as an Intervening Variable (Case Study of FEB Students, Bandar Lampung University) - Novitasari, Meidi; Barusman, Andala Rama Putra (CV. ITTC INDONESIA, 2025)
This study attempts how influencers, live streaming, EWOM, and flash sales influence purchase decisions using customer satisfaction as an intervening variable. A quantitative approach was used, employing surveys and questionnaires from 280 respondents. Structural Equation Modeling (SEM) with a PLS approach revealed that influencers positively and significantly influence purchase decisions, as their credibility, attractiveness, and popularity enhance consumer trust. Conversely, live streaming, EWOM, and flash sales were found to have no significant effect on purchase decisions, indicating that real-time interactions, positive reviews, and large discounts fail to sufficiently drive consumer interest in Jiera's products. It has been demonstrated that the link between these factors and purchase decisions is mediated by customer satisfaction. Furthermore, customer satisfaction significantly impacts purchase decisions, with satisfied consumers demonstrating loyalty and willingness to recommend products. This study provides insights for businesses to prioritize strategies that enhance consumer shopping experiences.